THE EFFECTIVENESS OF GUESING GAME TO TEACH SPEAKING AT RELIGION PROGAM OF STIT AL URWATUL WUTSQO JOMBANG - Khudriyah Khudriyah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Speaking as a process of constructing meaning, giving and receiving information is very important to own by students. But they often got problem in mastery it. This research is aimed to know whether or not guessing gams effective to teach speaking. Design of this study is quantitative, using test as collecting data, the data then analyzed using Kolmogrov Smirnov, since the data didn’t meet the normality test criteria. The result of the research is guessing game has not affected the students speaking ability of second grade of STIT al Urwatul Wutsqo Jombang. Based on the result of Z test is empirical Z is lower than theoretical Z, so the guessing games hasn’t affected the students speaking ability, that means there is no difference speaking ability between students who are taught using guessing game and practice method.